Pengaruh Pendidikan Terhadap Kinerja Karyawan di Moderasi Keterlibatan Karyawan - Yunatan, Rikardus Outniel; Gaspersz, Vincent; Manafe, Henny A. (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
This study aims to analyze the role of work involvement moderation from the direct relationship between education and employee performance in CV MSMEs. C & A in Kupang City. The population in this study was 64 employees which were then used as samples with census/saturated techniques. Data analysis techniques using moderation analysis with the help of SmartPLS version 3.30. The results showed that education directly has a positive and significant effect on employee performance, but work involvement does not moderate the relationship between education and employee performance.